Analisis Propaganda Kartel Sinaloa di Kawasan Amerika Latin: Indonesia - Rizal, Pandu Satya (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2023)
This article reviews in depth how propaganda is carried out by the Sinaloa Cartel in Latin America, in general this paper examines more deeply using the Jowett & Donell approach to Propaganda and Persuasion. The main purpose of this paper is to find out the propaganda carried out by Sinaloa. The method used is qualitative with a literature study approach, the main finding of this paper is that propaganda was successfully carried out by Sinaloa to strengthen its existence in Latin America, propaganda was carried out using images of violence and cruelty, the media often used were Tiktok, Narcobanners and Narcocorridos, the effectiveness of this propaganda turned out to be successful. Keywords: Cartel, Narcocorridos, Narcomantas, Propaganda, Sinaloa, Tiktok